Hematological Profile of Macaca nemestrina Across Different Age Groups - Sri Wahyuni; Fitriya Nur Annisa Dewi; Anita Esfandiari; Suryo Saputro; Huda Shalahudin Darusman (IPB University, 2025)
Macaca nemestrina, also known as the pigtail macaque, plays a crucial role in drug development and serves as a highly valuable animal model for studying various human diseases due to its phenotypic similarities to humans, including those related to the aging process. Hematology is a critical component of clinical assessments for this spesies, serving both as a diagnostic tool to determine their health status and to characterize disease models, including degenerative and geriatric diseases. As anemia is a common phenomenon in the elderly, it is also important to determine whether M. nemestrina exhibit a similar condition with age. The aim of this study was to determine the hematological profiles of clinically healthy female M. nemestrina across young, adult, and elderly age groups, particularly related to anemia parameters. This study was conducted at the Primate Research Center, IPB University, Bogor, Indonesia. The animals were part of a breeding colony and were divided into three groups based on age: young (5–7 years), adult (12–14 years), and elderly (18–21 years). Following anesthesia with ketamine, a physical examination was performed to determine clinical status, and blood samples were collected for a complete blood count (CBC) evaluation using an automated analyzer. The results showed that total erythrocytes, hemoglobin concentration, hematocrit value, and mean corpuscular hemoglobin (MCH) were significantly different (P<0.05) in the elderly group compared to the other groups. Additionally, the red cell distribution width (RDW) percentage and leukocyte count differed significantly between the adult and elderly groups. The results showed that the erythrogram differs with age in clinically healthy M. nemestrina, suggesting the importance of determining appropriate baseline reference values in macaques of different ages.